Dakwah STAIN Purwokerto KOMUNIKA ISSN: 1978-1261 Vol.3 No.2 Juli-Desember 2009 pp.167-183 GENDER DALAM KONSTRUKSI MEDIA - Hariyanto, Hariyanto (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2009)
Gender issues, the image of the relation of men and women in the media product, located at the position concurrence. While the media products that represent a certain meaning and reality to be submitted by his creator (media workers). Not infrequently, sense of product made through the media has put the position of media products as part of social reality itself.On the other hand, the position of the meaning of media products into the medium for the legitimacy of a change in governance norms and values in society. In other words, the image of the relation of men and women in the media products that contain sexual harassment can be carried still values the old conservative and applicable to the community that Indonesia is very patriarchy